The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fendo.2021.762691
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid-Induced Gut Microbiota Improves Metabolic Endotoxemia

Abstract: BackgroundCoffee can regulate glucose homeostasis but the underlying mechanism is unclear. This study investigated the preventive and therapeutic effects of chlorogenic acid (CGA), a polyphenol that is found in coffee, on obesity and obesity-related metabolic endotoxemia.MethodMale 4-week-old C57BL/6 mice were fed either normal chow or a high-fat diet or 20 weeks and half the mice in each group were gavaged with CGA. Oral glucose tolerance tests (OGTTs) and insulin tolerance tests (ITTs) were performed. Marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 50 publications
5
55
0
Order By: Relevance
“…In our study, Ruminococcaceae were remarkably increased in Lepr −/− rats via LWE intervention. In addition, Faecalibaculum is a group of gram-positive obligate anaerobe that can produce short-chain fatty acids, more specifically butyrate, through fermentation [ 56 , 57 ]. Intestinimonas is a representative genus producing butyrate [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, Ruminococcaceae were remarkably increased in Lepr −/− rats via LWE intervention. In addition, Faecalibaculum is a group of gram-positive obligate anaerobe that can produce short-chain fatty acids, more specifically butyrate, through fermentation [ 56 , 57 ]. Intestinimonas is a representative genus producing butyrate [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Microbiology frontiersin.org promising probiotics (Romano et 2021;Ye et al, 2021). Meanwhile, significant increases in Lachnospiraceae_NK4A136_ group (genus) and Firmicutes_bacterium_M10-2 (species) were also highlighted in the KO group compared with the WT group.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, when compared with WPbA, the biomarkers for KPbA included significantly increased Faecalibaculum (Faecalibaculum rodentium) and Dubosiell and decreased Akkermansia (Akkermansia_ muciniphila). Interestingly, these three genera/species microbiota were all beneficial for the production of short-chain fatty acids (SCFAs; Shen et al, 2021;Ye et al, 2021), which, as one of the safeguards for maintaining gut health, plays an important role in strengthening epithelial barrier integrity and inhibiting inflammation. However, a previous study found that oral administration of F. rodentium in antibiotic-treated resilient Ephx2 KO mice led to depression-like behaviors (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Genus Dubosiella is a member of shortchain fatty acid (SCFA) producers (Mao et al, 2019;Bojovic et al, 2020). A previous study showed that chlorogenic acid increased the abundance of Dubosiella and improved metabolic endotoxemia (Ye et al, 2021). In contrast, the protective effects of yellow wine polyphenolic compounds were associated with a lower abundance of Dubosiella in Dox-treated rats (Lin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%